2023
DOI: 10.1101/2023.03.14.532627
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

State-dependent GABAergic regulation of striatal spiny projection neuron excitability

Abstract: Synaptic transmission mediated by GABAA receptors (GABAARs) in adult, principal striatal spiny projection neurons (SPNs) can suppress ongoing spiking, but its effect on synaptic integration at sub-threshold membrane potentials is less well characterized, particularly those near the resting down-state. To fill this gap, a combination of molecular, optogenetic, optical and electrophysiological approaches were used to study SPNs in mouse ex vivo brain slices, and computational tools were used to model somatodendr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
2
0
0
Order By: Relevance
“…The results clearly imply that when the starting point of the initiated plateau response is below the chloride equilibrium potential for GABA (set to −65 mV), the GABA input will initially provide a depolarization that can facilitate the plateau response, but if it starts above the equilibrium potential, it will instead reduce the amplitude. This excitatory effect of GABA has previously been observed ( 22 , 23 ). May et al ( 23 ) demonstrated that optogenetic and GABA uncaging led to depolarization in SPNs.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The results clearly imply that when the starting point of the initiated plateau response is below the chloride equilibrium potential for GABA (set to −65 mV), the GABA input will initially provide a depolarization that can facilitate the plateau response, but if it starts above the equilibrium potential, it will instead reduce the amplitude. This excitatory effect of GABA has previously been observed ( 22 , 23 ). May et al ( 23 ) demonstrated that optogenetic and GABA uncaging led to depolarization in SPNs.…”
Section: Resultssupporting
confidence: 80%
“…This excitatory effect of GABA has previously been observed ( 22 , 23 ). May et al ( 23 ) demonstrated that optogenetic and GABA uncaging led to depolarization in SPNs.…”
Section: Resultssupporting
confidence: 80%